Optimum design of tied-arch bridges under code requirements using enhanced artificial bee colony algorithm. (September 2019) - Latif, M.A.; Saka, M.P.
Highlights: Optimum design algorithm developed for tied-arch bridges using 3-D modeling in order to consider the lane loading for vehicles. The proposed algorithm considers AASHTO-LRFD provisions and uses influence lines to generate the internal force actions for moving vehicle loads in the design. The algorithm does not use readymade hot rolled sections but built-up I and/or box sections. The design process employs rectangular steel plates for constructing built-up sections. Use of indirect design variables. Steel plates sections are treated as design variables which are used to construct built-up I and/or box sections that are main design variables. Enhancement proposed for the artificial bee colony algorithm attains lower values of the final solutions compared to the standard artificial bee colony algorithm. Abstract: In this study, optimum design algorithm is presented for tied-arch bridges under AASHTO-LRFD Bridge Design Specifications provisions. It is decided that in tied-arch bridges ties, arch ribs, and bottom and top bracings are made of built-up box sections, whereas built-up I sections are utilized for floor beams and stringers. Bars are adopted for hangers. In the formulation of the optimization problem, design variables are selected as the cross sectional dimensions of steel plates not that of I and box sections. Design pools are prepared for steel plate sections in addition to the hanger bars so that the optimization algorithm can select appropriate steel plates, construct I and box built-up sections for members of 3-D tied-arch such that the weight of the bridge is minimized. In addition to design code requirements, geometrical constraints among its elements that are required for manufacturability of the bridge are also considered. The design process of tied-arch bridges differs from that of steel framed structures. It necessitates consideration of moving vehicle loads. Design optimization algorithms require the response of bridges under several design load arrangements and in the construction of influence lines. This is achieved by using open application programming interface (OAPI) facility of SAP2000. The solution of discrete nonlinear programming problem is obtained by using the proposed Enhanced Artificial Bee Colony algorithm (eABC). The proposed algorithm is compared with Standard Artificial Bee Colony (ABC) and Exponential Big Bang-Big Crunch (eBB-BC) algorithms to evaluate its performance.